2021
DOI: 10.7717/peerj.12171
|View full text |Cite
|
Sign up to set email alerts
|

Integrative bioinformatics and experimental analysis revealed down-regulated CDC42EP3 as a novel prognostic target for ovarian cancer and its roles in immune infiltration

Abstract: Ovarian cancer is a significant clinical challenge as no effective treatments are available to enhance patient survival. Recently, N6-methyladenosine (m6A) RNA modification has been demonstrated to play a pivotal role in tumorigenesis and progression. However, the roles of m6A target genes in ovarian cancer haven’t been clearly illustrated. In this study, we presented a comprehensive bioinformatics and in vitro analysis to evaluate the roles of m6A target genes. Cell division cycle 42 effector protein 3 (CDC42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…Previous studies have indicated that the bio functional roles of CDC42EP3 in regulating cell shape change, actomyosin contractility and pathological fibroblast activation ( Farrugia and Calvo, 2016 ). Additionally, CDC42EP3 is also associated with the occurrence and progression of human cancers, such as colorectal cancer ( Feng et al, 2021 ), ovarian cancer ( Yan et al, 2021 ), and glioma ( Yang et al, 2022 ). HIST1H4L, known as H4 Clustered Histone 13 (H4C13), is essential nuclear proteins responsible for the nucleosome structure of the chromosomal fiber in eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that the bio functional roles of CDC42EP3 in regulating cell shape change, actomyosin contractility and pathological fibroblast activation ( Farrugia and Calvo, 2016 ). Additionally, CDC42EP3 is also associated with the occurrence and progression of human cancers, such as colorectal cancer ( Feng et al, 2021 ), ovarian cancer ( Yan et al, 2021 ), and glioma ( Yang et al, 2022 ). HIST1H4L, known as H4 Clustered Histone 13 (H4C13), is essential nuclear proteins responsible for the nucleosome structure of the chromosomal fiber in eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…M6A methylation mechanism have greatly contributed to the field of epigenetics. Methyltransferases, demethylases, and reading proteins jointly regulate m6A levels in downstream genes, thereby promoting tumor initiation and progression ( Xu et al, 2020b ; Yan et al, 2021 ). M6A RNA methylation comprises the m6A methyltransferase, m6A demethylase, and m6A binding proteins which regulate mRNA precursor shear, mRNA stability, and translation.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…Yan et al also reported cell division cycle 42 effector protein 3 (CDC42EP3) as a possible target gene of m 6 A, which was downregulated by m 6 A regulators in the OC cells and tissues [ 80 ]. Interestingly, the expression of CDC42EP3 was reported to be correlated with the various TICs, including natural killer cells, T central memory cells, and T gamma delta cells [ 80 ]. Jiang et al further elucidated the mechanism of m 6 A regulatory factors involved in immune responses [ 54 ].…”
Section: A and Ocmentioning
confidence: 99%